Ultimate channel capacity analysis of the UCA-OAM system with a deficient-rank channel matrix - Ma, Qian; Yu, Xiaoyou; Tu, Li; Lu, Zukun (Frontiers in Physics, 2023)
The channel matrix of the commonly used uniform circular array based orbital angular momentum (UCA-OAM) system is full-rank state when the degree of freedom (DoF) is limited only by the number of UCA antenna elements. The rank of the channel matrix of the UCA-OAM system is equal to the DoF at this condition. However, the practical DoF of the UCA-OAM system is always affected by other transmission factors, such as the transmission distance and the radius of the receiving antenna, etc. Therefore, by exploiting the practical DoF of the UCA-OAM system affected by transmission distance, the radii of the receiving antenna and transmission antenna, a novel channel capacity model of UCA-OAM communication system with deficient-rank channel (DRC) matrix is first proposed. Moreover, the formulas of channel matrix and channel capacity for DRC matrix are analytically derived. The results of numerical simulations indicate that when the the practical transmission factors including transmission distance, the radii of the receiving antenna and transmission antenna are considered, the UCA-OAM communication system with DRC matrix has less channel capacity than that with full-rank channel (FRC) matrix. These simulated results will give a helpful guide for the practical application of UCA-OAM communication system.